Neuro-protective roles of long non-coding RNA MALAT1 in Alzheimer's disease with the involvement of the microRNA-30b/CNR1 network and the following PI3K/AKT activation - Li, Li; Xu, Yuelong; Zhao, Meng; Gao, Zhiqiang (Experimental and molecular pathology, 2020)
Long non-coding RNAs (lncRNAs) have been increasingly found to fulfill key functions in neurodegenerative diseases. This study aimed to probe the function of lncRNA MALAT1 in neuronal recovery in Alzheimer's disease (AD). Aβ25-35 was used to induce AD in a rat model and neuronal injury in PC12 and C6 cells. Aberrantly expressed lncRNAs/microRNAs (miRNAs) in AD rats were screened out by microarray analyses. Altered expression of MALAT1, miR-30b and CNR1 was performed to explore their roles in neuronal recovery in rat and cell models. Consequently, LncRNA MALAT1 and CNR1 were poorly expressed while miR-30b was highly expressed in Aβ25-35-induced rat models and cells. Overexpression of MALAT1 or CNR1 reduced neuronal injury in rat hippocampus. It increased viability and decreased apoptosis in injured PC12 and C6 cells, and decreased the secretion of pro-inflammatory factor IL-6 and TNF-α but increased IL-10 production. However, overexpression of miR-30b reversed these trends. MALAT1 could served as a sponge for mR-30b to up-regulate CNR1 expression. The phosphorylation of PI3K and AKT was stimulated when MALAT1 or CNR1 was overexpressed. To sum up, we found MALAT1 could promote neuronal recovery following AD through the miR-30b/CNR1 network and the PI3K/AKT signaling activation.